OOO! THE PORTRAYAL OF WEREWOLVES IN HARRY POTTER, TWILIGHT SAGA, AND TEEN WOLF - Al Khansa, Rona Zhafira; Nuraini, Nabilla Intan; Azfa Alfarisi, Muhammad (HUMANIS: Jurnal Ilmu-Ilmu Sosial dan Humaniora, 2025)
This study investigates the portrayal of werewolves across three distinct cinematic franchises: ‘Harry Potter, ‘Twilight Saga’, and ‘Teen Wolf’. The research examines how these films visually and narratively depict werewolves, analyzing their transformation, identity, and symbolism. Employing a descriptive qualitative methodology, the study integrates visual analysis techniques, focusing on the denotative and connotative meanings of visual representations. This study applies techniques of analysis by Spradley (2016) which consist of four steps: domain, taxonomy, componential, and cultural theme. Harry Potter frames the werewolf as a tragic figure, emphasizing stigma and societal exclusion through Remus Lupin’s humanoid transformation. The Twilight Saga reimagines werewolves as symbols of cultural heritage and guardianship, reflected in their full wolf forms tied to the Quileute tribe. In contrast, Teen Wolf presents a spectrum of forms: humanoid, hybrid, and wolf. Exploring themes of self-discovery, hierarchical structures, and the balance between human and wolf instincts. These portrayals collectively underscore the evolving representation of werewolves from monstrous beings to complex characters grappling with personal and societal conflicts. This research contributes to a deeper understanding of anthropomorphic narratives, offering a comparative perspective on the cultural and symbolic significance of werewolves in contemporary media.